Willingness to pay for Beach Ecosystem Services: The case study of three Colombian beaches. (1st July 2018) - Enriquez-Acevedo, T.; Botero, Camilo M.; Cantero-Rodelo, R.; Pertuz, A.; Suarez, A.
Abstract: Throughout the scientific literature, beaches have been regarded as very valuable ecosystems for the tourism industry; however, these ecosystems provide multiple direct and indirect benefits beyond tourism. This paper accounts for the results from a Willingness to Pay (WTP) study using data from 425 respondents at three beaches in the Colombian Caribbean Region. Out of the respondents from the three beaches, over 70% expressed a positive WTP to maintain Beach Ecosystem Services (BES) beyond tourism purposes. At two beaches, the payment amount was 3.40 US/month, while at the third beach the payment amount was 6.80 US/month. Beach environmental quality seemed to be an important aspect regarding the payment amount. It is highlighted that WTP in beaches did not depend on economic variables such as income or employment, whereas variables related to perception had a determining impact. WTP for BES was defined by interest in environmental issues and concerns about ecosystem services loss. The results offered hereto could provide support to decision makers through quantitative information on social preferences regarding beach improvement projects policies, if several reflections are considered.